Identifying the groups becomes harder when the degradation chain is long, especially for groups catalyzing upstream reactions. - Yuanchen Zhao (12905580) (2024)
(A) The panel shows the ability of the Metropolis algorithm to recover the true functional groups within a linear degradation chain with N = 4 metabolites. The recovery quality of a group is defined as the Jaccard Similarity between the true functional group and its closest match in the algorithm output. Here, the recovery qualities of each of the true functional groups (groups 1, 2, and 3) are shown as a function of k, the number of groups requested from the algorithm. Recovery qualities attained by random k-group groupings are shown as controls (black line with triangle markers). As the number of groups k in the output increases, the algorithm first finds group 3 (direct producers), then group 2 and group 1, with ever-decreasing recovery quality. (B) The recovery quality of Metropolis of the most upstream group (group 1, blue dashed line) and the direct producers (group N − 1, red solid line) in the N-metabolites degradation chain, shown as a function of N. Recovery quality of group 1 is reported for N-group algorithm outputs while that of direct producers is for 2-group outputs (see text.) As controls, the recovery qualities (of arbitrary group) by N-group and 2-group random groupings are shown as black dashed line and black solid line, respectively. As the chain becomes longer, the ability to recover the most upstream group drops quickly, whereas the direct producers are adequately recovered up to length 5. In both panels, shading indicates the standard error of the mean over 50 synthetic datasets, circles indicate data points for Metropolis while triangles for random groupings.